The importance of intestinal microbial flora (microbiota) and role of diet - Tomasello, Giovanni; Sorce, Alessandra; Damiani, Provvidenza; Sinagra, Emanuele; Carini, Francesco (Progress in Nutrition, 2017)
In this article we want to analyze the function of the intestinal microbial flora. In the intestinal environment microorganisms “good” microorganisms coexist with “bad”. The coexistence between good and bad bacteria is balanced by a mutual action of contrast that has the purpose of maintaining the intestinal microbial flora in a state of equilibrium. This condition is referred eubiosis. This article will attempt to analyze the beneficial role carried out by eubiotic microbial flora showing the negative effects of dysbiosis.